MENANAMKAN TRADISI MEMBACA PADA SISWA MENURUT PANDANGAN KH. WAHID HASYIM DALAM MENJAWAB TANTANGAN ERA INDUSTRI 4.0 - Zaenani Qodriyatun; Muqowim Muqowim; Radjasa Radjasa (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
Abstract : This library research study attempts to answer two questions. First, how had KH. Wahid Hasyim thought about character education? Second, how the character implementation likes reading according to KH. Wahid Hasyim on the current condition of reading power in Indonesia, especially madrasa students? Through inductive analysis, two findings are produced. First, there are eight character values that educated by KH. Wahid Hasyim. The eight values are religious, tolerance, self-attendance, democratic, nationalism, love for the motherland, friendly or communicative, and fond of reading. The second finding in this study, that the fondness of reading KH. Wahid Hasyim is in line with what is contained in the Law on the National Education System (National Education System) No. 20 of 2003 article 4 paragraph 5 which explains that education is carried out by developing a culture of reading, writing and arithmetic for all citizens. Also in line with the command of Allah in the teachings of Islam contained in the first revelation that is